Housing transformation's delivery potential in developing economies - Mai Mai, M. M.; Shamsuddin, S. (2007)
The twenty first century witnessed a proliferation of concepts and models of new housing development especially in industrialized countries. As such, these are manifestations of their kind of housing transformation. Developing societies on the other hand, experienced more of alterations, and extensions of residential units in urban environment, in response to rural urban population shift. Both societies' transformations involve shaping the built form physically, moderated by social and psychological motives. It could be argued that a conceptual framework of the built environment derived from a variety of influences: structural context, the mediating role of institutions and agencies (like development control), the individual and collective human actions, and their contextual representations. A case study qualitative research of urban fringes traces the characters of an indigenous housing pattern impacted by rapid urbanization, due to a political decision. These transformations in three decades and their motivations are chronologically evaluated. The result is a social theory rooted in the built environment disciplines, to elucidate how and why we build places and dwell in spaces that are once contradictory, conforming, liberating and illuminating. It clearly shows a significant increase in housing supplyin a variety of occupancy, within the same lateral space.